2016
DOI: 10.1055/s-0036-1588008
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Reclassification of Glycemic Status in Women with Gestational Diabetes Mellitus and Associated Risk Factors

Abstract: T2DM was diagnosed in 34 (12.2%) patients, IFG in 58 (20.8%), and IGT in 35 (12.5%). Women with postpartum T2DM showed more frequently a family history of T2DM, higher pre-pregnancy body mass index (BMI), lower gestational age, higher fasting and 2-hour plasma glucose levels on the OGTT at the diagnosis of GDM, higher levels of hemoglobin A1c, and a more frequent insulin requirement during pregnancy. Paternal history of T2DM (odds ratio [OR] = 5.67; 95% confidence interval [95%CI] = 1.64-19.59; p = 0.006), fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…38 Outros desenhos feitos também estão de acordo com essa associação, como uma pesquisa coorte envolvendo 279 mulheres com DMG concluiu que mulheres cujas mães tiveram diabetes mellitus tipo 2 tinham maiores chances de desenvolver diabetes mellitus tipo 2 no pós-parto (0=0,009). 39 Entretanto, alguns estudos não comprovaram tal associação. Uma pesquisa envolvendo 366 mulheres com histórico de diabetes gestacional concluiu que um histórico familiar de diabetes e um histórico pessoal de diabetes gestacional em gravidez prévia não foram fatores que não tiveram associação estatística com o desenvolvimento de tolerância anormal à glicose (p valor foi respectivamente 0,24 e 0,14).…”
Section: Resultsunclassified
“…38 Outros desenhos feitos também estão de acordo com essa associação, como uma pesquisa coorte envolvendo 279 mulheres com DMG concluiu que mulheres cujas mães tiveram diabetes mellitus tipo 2 tinham maiores chances de desenvolver diabetes mellitus tipo 2 no pós-parto (0=0,009). 39 Entretanto, alguns estudos não comprovaram tal associação. Uma pesquisa envolvendo 366 mulheres com histórico de diabetes gestacional concluiu que um histórico familiar de diabetes e um histórico pessoal de diabetes gestacional em gravidez prévia não foram fatores que não tiveram associação estatística com o desenvolvimento de tolerância anormal à glicose (p valor foi respectivamente 0,24 e 0,14).…”
Section: Resultsunclassified
“…37 Also, earlier studies done in Brazil and Iran demonstrated that overt postpartum diabetes mellitus and IGT were 8.1% and 21.4%, respectively, while 70.5% restored normoglycemic state. 38,39 However, some other studies reported a lower prevalence rate of diabetes that ranged from 2-8%. [40][41][42]…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus usually resolves after delivery, as hormones secreted from the placenta, as the main source of insulin resistance, are removed from the body (39). Therefore, the need for drug therapy mostly resolves after delivery although these patients are at risk of type 2 diabetes, which may occur in 50% of women in the next 20 years (40,41).…”
Section: Recommendation 35mentioning
confidence: 99%